Hemolytic events after the administration of lyophilized versus liquid immune globulin: an analysis of a single manufacturer's safety database. Issue 8 (13th April 2015) - Berg, Roger; Jacob, Dalia; Fuellenhals, Elisabeth
<x xml:space="preserve">Abstract</x> BACKGROUND Recent publications have raised concerns that liquid immune globulins (IGs) may be associated with either a higher or a lower frequency of hemolytic events compared to lyophilized IGs, among other reasons due to the differences of their isohemagglutinin content. The aim of this study was to evaluate the relationship of hemolytic events to product presentation (liquid versus lyophilized) and to examine the relationship between total IG doses administered and the individual isohemagglutinin titers of IG lots infused. STUDY DESIGN AND METHODS The reporting rate as well as the proportional reporting rate (PRR) of hemolytic events for liquid (Gammagard liquid [GGL]) and lyophilized IG (Gammagard S/D [GGSD]) received spontaneously from the United States was calculated. For all hemolytic events received spontaneously from global sources, total IG doses (g/kg body weight) and the loading dose of isohemagglutinins (total IG dose infused × isohemagglutinin titers of infused lots) were determined. RESULTS With 0.27 and 0.33 cases per 1 million grams distributed, the reporting rates for GGL and GGSD are comparable, further confirmed by a PRR of 1.0 (95% confidence interval, 0.4‐2.7). Hemolytic events for GGL and GGSD were observed with low loading doses of isohemagglutinins, and lots with high isohemagglutinin titers did not contribute to the development of hemolytic events in a higher proportion than lots with low titers CONCLUSIONS Hemolysis associated with GGL or GGSD can occur even with low loading doses of isohemagglutinins. Data presented do not indicate that high isohemagglutinin titers of IG products play a major role in the development of these events.